OLD TOWN OF HERACLEA SINTICA - ARCHAEOLOGICAL HERITAGE ADAPTATION IN SOUTHWEST OF BULGARIA - Ivanov, Sotir (Revista Inclusiones, 2020)
This text looks at the history of the ancient city Heraclea Sintica and more specifically archaeological work and historical research. In the late eighteenth and early nineteenth centuries, for the first time they tried to locate the historic city. With time and interest a scientific discussion began which ended successfully in 2002, after the discovery of the imperial letter made by Galerio and Maximin Daza in Kozhuh, Petrich Municipality in the southwestern part of Bulgaria.